Verknader av digitalisering på materialvurdering, redaksjonell metode og opplæring - Grønvik, Oddrun (Nordiske Studier i Leksikografi, 2006)
Effects of digitisation on the use of source materials, editorial method and editorial training. Digitisation of Norway’s largest academic dictionary project, Norsk Ordbok 2014, through an interlinked set of relational databases has led to new ways of using source materials in lemma selection, manuscript management and quality control. Editorial method is radically changed by increased transparency, both in looking at source materials and in handling dictionary and entry formats. These changes are prerequisites for training linguists to become productive editors within a minimal time span, with six months for basic training and full editorial responsibility after one year. The aim of the exercise is to complete seven volumes of Norsk Ordbok in nine years, with no loss of, and preferably an increase in, quality.